Effect of Alcohol on Hippocampal-Dependent Plasticity and Behavior: Role of Glutamatergic Synaptic Transmission - Mira, Rodrigo G.; Lira, Matias; Tapia-Rojas, Cheril; Rebolledo, Daniela L.; Quintanilla, Rodrigo A.; Cerpa, Waldo (Frontiers in Behavioral Neuroscience, 2020)
Alcohol problematic drinking and alcohol dependence are an increasing health problem worldwide. Alcohol abuse is responsible for approximately 5% of the total deaths in the world, but its addictive consumption has a substantial impact on neurological and memory disabilities throughout the population. One of the better-studied brain areas involved in cognitive functions is the hippocampus, which is also an essential brain region targeted by ethanol. Accumulative evidence in several rodent models has shown that ethanol treatment produces cognitive impairment in hippocampal-dependent tasks. These adverse effects may be related to the fact that ethanol impairs cellular and synaptic plasticity mechanisms, including adverse changes in neuronal morphology, spine architecture, neuronal communication, and finally, an increase in neuronal death. There is evidence that the damage that occurs in the different brain structures is differential according to the stage of development in which the subjects are exposed to ethanol, and even more early exposure would cause damage in the adult stage. Studies of the cellular and cognitive deficiencies produced by alcohol in the brain are needed for the search for new strategies to reduce alcohol neuronal toxicity and for the understanding of its consequences on memory and cognitive performance with emphasis on crucial stages of development, from prenatal events to adulthood.